Factors of using waste as fuel in thermal energy systemsof Part 2. Design and operation features of the equipment for solid waste burning - Kolienko, A.; Shelimanova, O.; Biletskyi, D. (Energy and Automation, 2023)
The use of solid household waste (SHW) as an energy raw material is one of the promising ways to solve the problem of accumulation of production and consumption waste. In recent decades, the share of solid waste, which is burned with the utilization of materials and heat, has been steadily increasing. However, since the composition of SHW and their combustible characteristics are significantly different from other known types of solid fuel, it is necessary to reconstruct the existing solid fuel heating boilers.The purpose of the study is to develop recommendations for the reconstruction of existing solid fuel circuits for the safe and efficient organization of the solid waste burning process.It is shown that in order to achieve complete combustion of the fuel and minimal emissions of the dispersed phase when burning solid waste, it is necessary to ensure a high flame temperature, the presence of an oxidizing medium and a significant volume of the furnace.The requirements for the arrangement of systems for cleaning combustion products from devices intended for solid waste incineration are given.Additional requirements for organizing the operation of fuel combustion systems using SHW are substantiated.Key words: incineration of solid household waste, cleaning of combustion products, operation of fuel combustion systems